If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -19 + -11x + 12x = 5 Combine like terms: -11x + 12x = 1x -19 + 1x = 5 Solving -19 + 1x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + 1x = 5 + 19 Combine like terms: -19 + 19 = 0 0 + 1x = 5 + 19 1x = 5 + 19 Combine like terms: 5 + 19 = 24 1x = 24 Divide each side by '1'. x = 24 Simplifying x = 24
| 5x+6(x-3)=42 | | 33=(3x-28)+(3x-30)+x | | 16=5a-9 | | 4(x+3)=6(3-x) | | 6x-24-4x=6 | | 5y+2x=3y-x | | 3x-1=2x-4+(2x-3-2) | | 3(n+1)=5n-3-2n | | 7(4.33)+2= | | 1.7p-3=0.9p+13x | | 0.5(2x-5)=4x-1 | | 5x+2y=3x-y | | 27+x-(3x+47)=x+26-10 | | 27+x-(3x-28)=x+26-10 | | (-2x+4)-(9x+1)= | | 14-9x=62-3x | | 4x+5x-102=69 | | (-8-5)-6-2= | | -5(1-5x)*5(-8x-2)=-4x-8x | | 3s=4r | | -8=4(y-5)-8y | | 0.75w-5=1-0.20w | | 2x+3=64 | | 1/12+9/16= | | 1/12+9/16=x | | 24-5y=14 | | (2z+3)+3(5-3z)= | | 3.6x=48.24 | | 11+3x= | | 4x-29=13+6+2x-18 | | (8x-3)+(-4x+2)= | | -23=3e(-9) |